Major Hepatic Trauma: Warm Ischemic Tolerance of the Liver After Hemorrhagic Shock - Perdrizet, George A.; Giles, David L.; Dring, Robert; Agarwal, Suresh K.; Khwaja, Khalid; Gao, Yuan Z.; Geary, Michael; Cowell, Vernon L.; Berman, Martin; Brautigam, Robert (The Journal of surgical research, 2006)
The management of severe hepatic trauma frequently involves exposing the liver to varying periods of warm ischemia. The ischemic tolerance of the liver, in the setting of hemorrhagic shock (HS) and trauma, is presently unknown. We tested the hypothesis that warm ischemic tolerance of the porcine liver will be decreased following resuscitation from HS. Twenty-three Yorkshire pigs were divided into three groups: 1) hepatic ischemia alone (HI, n = 9); 2) hemorrhagic shock alone (HS, n = 3); and 3) hemorrhagic shock plus hepatic ischemia combined (HSHI, n = 11). Following reperfusion, a liver biopsy was obtained and serial blood chemistries were sampled. Post-operative day 7 mortality was increased in the HSHI group (7/11) compared to the HI (0/9) group, P = 0.038. Notably, deaths did not result from acute liver failure, but rather from intra-operative hemodynamic collapse shortly following hepatic reperfusion. In addition, the HSHI group experienced significantly elevated lactic acid, serum creatinine and liver enzyme levels. Analysis of the liver biopsy samples is consistent with a more severe liver injury in the HSHI group. The warm ischemic tolerance of the liver following resuscitation from HS is significantly decreased in this porcine model compared to HS or HI alone. Mortality was associated with acute intra-operative hemodynamic collapse occurring shortly after hepatic reperfusion.